2019
DOI: 10.1073/pnas.1900997116
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA LINC00673-v4 promotes aggressiveness of lung adenocarcinoma via activating WNT/β-catenin signaling

Abstract: It is well recognized that metastasis can occur early in the course of lung adenocarcinoma (LAD) development, and yet the molecular mechanisms driving this capability of rapid metastasis remain incompletely understood. Here we reported that a long noncoding RNA, LINC00673, was up-regulated in LAD cells. Of note, we first found that LINC00673-v4 was the most abundant transcript of LINC00673 in LAD cells and its expression was associated with adverse clinical outcome of LAD. In vitro and in vivo experiments demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 49 publications
4
81
0
Order By: Relevance
“…LncRNAs have been shown to play important roles and to act through multiple mechanisms, including as ceRNAs, in a variety of cancers [46][47][48]. There is still some controversy regarding the role of LINC00673 in carcinogenesis, numerous studies have described LINC00673 as either a tumor suppressor or promoter [11][12][13][14][15]. Although previous studies have also identified the oncogenic role of LINC00673 was upregulation in breast cancer tissues and related with patients' prognosis [19], very little is known about the molecular mechanisms of LINC00673 in breast cancer carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs have been shown to play important roles and to act through multiple mechanisms, including as ceRNAs, in a variety of cancers [46][47][48]. There is still some controversy regarding the role of LINC00673 in carcinogenesis, numerous studies have described LINC00673 as either a tumor suppressor or promoter [11][12][13][14][15]. Although previous studies have also identified the oncogenic role of LINC00673 was upregulation in breast cancer tissues and related with patients' prognosis [19], very little is known about the molecular mechanisms of LINC00673 in breast cancer carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that LINC00673 is a potential tumor suppressor whose germline variation is associated with pancreatic cancer risk [10]. Conversely, LINC00673 was identified to play a role in tumorigenesis in a variety of malignancies [11][12][13][14][15]. A rapidly growing number of studies have suggested that cytoplasmic lncRNAs are essential mediators of intracellular signaling pathways and are involved in regulating mRNA stabilization and transport as well as microRNA sponging [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Due to unknown pathogenesis, the mortality of LUAD patients is still high and the treatment outcome is also unsatisfactory ( 27 ). In recent years, lncRNAs have played a more significant role in the development of tumors and the disorder of lncRNA may be considered as a crucial factor in the activities of tumors ( 28 , 29 ). We have found that lncRNA participated in 33 kinds of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Other lncRNAs that work as a suppressor include MEG3, interaction with p53 to downregulate β-catenin [260], and AK126698, negative regulation of FZD8 [221]. Alternatively, Guan and colleagues found that the overexpression of the lncRNA LINC00673-v4 was found to activate the Wnt/β-catenin pathway, noted by the enhanced interaction between DDX3 and CK1ε essentially leading to enhanced signaling of the pathway in lung adenocarcinoma cells [222]. With the overexpression of β-catenin and β-catenin transcriptional activity by SDH5 (ETC component) inhibition, cancer metabolism can be altered through the mediation of Wnt EMT and metastasis [261].…”
Section: Wnt/β-cateninmentioning
confidence: 99%